Análise de redes sociais de colaboração em bancas de defesa de doutorado na Pós-Graduação em Ciência da Informação - Telmo, Flávia de Araújo (2019)
The social networks of knowledge production, the forms of collaboration among researchers, the constitution of networks and the dynamic of social interactions become subjects of interest of scientific communities that deal with information. Analyzing the participation in examination boards is constituted in an opportunity of knowing the inherent characteristics to the actors of a social network in which they are linked, the developed researches, the factors that influence relations, the thematic interests of scientific researches, the interconnection between programs and institutions, and the way how the areas are consolidated and expand partnerships in the sharing of knowledge to the scientific development, mainly by the interdisciplinarity. In this context, the study analyzes the collaboration social network in examination boards of doctorate in the Graduate Program in Information Science of the Federal University of Paraíba (PPGCI/UFPB). Methodologically, it is founded from the objectives as a document and descriptive research with quantitative and qualitative approach. Formularies were adopted in data collection, and the MS Excel was used in the elaboration of Excel sheets. The mining of data adopted the Vantage Point, and the matrixes and graphs were done by using the Ucinet and the Netdraw. The results were analyzed under the perspective of the social network analysis methodology. The analysis of these collaboration networks resulted in the characterization of the members and of the structure of thesis defenses, as well as in the comprehension of the relations between actor and network established in the examination boards of the doctorate in the PPGCI/UFPB from 2015 to the semester 2018.1. It is identified that the interaction and the dialogic communication between the members of the examination boards in the mentioned Program is effected under formal rules and research interests inherent to the actuation of these members, research lines and academic background, which provides for the development of the program as well as the quality of its actions in academic scope that are periodically analyzed. o que proporciona o desenvolvimento do programa bem como a qualidade de suas ações no âmbito acadêmico que são avaliadas periodicamente. It is emphasized the constitution of networks with relations of researchers with external programs, as well as national institutions and interinstitutional. It is concluded that the collaboration network in examination boards of doctorate in the PPGCI/UFPB permits the sharing of information and the expansion of knowledge in networks among these actors and the opportunity of new collaborative partnerships.